The causes and consequences of pest population variability in agricultural landscapes. Issue 5 (16th May 2022) - Paredes, Daniel; Rosenheim, Jay A.; Karp, Daniel S.
Abstract: Variability in population densities is key to the ecology of natural systems but also has great implications for agriculture. Farmers' decisions are heavily influenced by their risk aversion to pest outbreaks that result in major yield losses. However, the need for long‐term pest population data across many farms has prevented researchers from exploring the drivers and implications of pest population variability (PV). Here, we demonstrate the critical importance of PV for sustainable farming by analyzing 13 years of pest densities across >1300 Spanish olive groves and vineyards. Variable populations were more likely to cause major yield losses, but also occasionally created temporal windows when densities fell below insecticide spray thresholds. Importantly, environmental factors regulating pest variability were very distinct from factors regulating mean density, suggesting variability needs to be uniquely managed. Finally, we found diversifying landscapes may be a win–win situation for conservation and farmers, as diversified landscapes promote less abundant and less variable pest populations. Therefore, we encourage agricultural stakeholders to increase the complexity of the landscapes surrounding their farms through conserving/restoring natural habitat and/or diversifying crops.